The Gondou hydrothermal field in the Ryukyu Arc: A huge hydrothermal system on the flank of a caldera volcano. (18th September 2017) - Minami, H.; Ohara, Y.
Abstract: High‐resolution geophysical mapping was conducted from an autonomous underwater vehicle on the flank of Daisan‐Kume Knoll in the Ryukyu Arc, southwest of Japan. 1 m resolution bathymetry identified 264 spires, 173 large mounds and 268 small mounds within a depression that is up to 1600 m wide and up to 60 m deep, at water depths between 1330 and 1470 m. Hydrothermal venting is strongly inferred from the observation of plumes in sidescan sonar imagery and positive temperature anomalies over the spires and mounds. This field, named the Gondou Field, has a giant mound G1 with a diameter of 280 m and a height of 80 m. Mound G1 has distinctive summit ridges composed of multiple spires where acoustic plumes with temperature anomalies up to 1.12°C are observed, indicative of high‐temperature venting. Other than mound G1, a number of active large mounds more than 30 m wide and spires over 10–22 m tall are common and they concentrate in the central and southern areas of the field, suggesting that these areas are the center of present hydrothermal activity. Acoustic plumes imaged by side‐scan sonar at the Gondou Field are different in character from bubble plumes imaged in other hydrothermal fields in the Ryukyu Arc. The plumes are diffused and deflected as they rise through the water column and have a shape consistent with black smokers. Key Points: A major hydrothermal field was discovered within a depression on the flank of Daisan‐Kume Knoll in a rifted‐arc Hundreds of active mounds and spires were found using 1 m resolution AUV bathymetry, sidescan, and temperature data The evolution processes of mounds in the Gondou Field were proposed based on the morphological observations